IMPACTS OF WETLAND DEGRADATION IN NIGER DELTA NIGERIA AND ITS SIGNIFICANCE IN FLOOD CONTROL - Loveline, Enwere Chidimma (International Journal of Environment, 2015)
Wetlands perform a wide variety of functions that include flood control, ground water recharge, shore line stabilization, storm protection and climate moderation. However, despite these huge wetland functions, it has witnessed poor appreciation and dreadful conditions. Niger Delta has witnessed constant coastal erosion and rising sea level, this has led to large portions of the landmass being eroded. This paper aims to review some environmental effects of flooding in the Niger Delta region of Nigeria to provide the desired knowledge of role that wetlands play in reducing flood impacts. However, having witnessed the flood, the experience opened my eyes to the environmental challenges facing Niger Delta with respect to Wetlands degradation, poor perception of wetland values and functions, poor environmental practices and non-implementation of environmental regulations. This memorable experience rekindled the desire and motivation to seek a solution to wetland degradation with the aim of recognizing significance of wetlands at the centre of achieving both livelihood and biodiversity improvements to address coastal flooding problem.The study therefore concludes that wetlands are very significant in flood control and thus the conservation and restoration of wetlands, should put in place measures to reduce wetland destruction. International Journal of Environment Volume-4, Issue-3, June-August 2015 Page: 177-184